PENGARUH DISIPLIN BELAJAR DAN MINAT BELAJAR TERHADAP PRESTASI BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN KEWARGANEGARAAN KELAS XI SMA NEGERI 1 PEMATANGSIANTAR T.A. 2024/2025 - Budiman Alvenson Purba; Sepriandison Saragih; Sabar Dumayanti Sihombing (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The formulation of the problem to be answered through this study is: (1) How do learning discipline and learning interest influence the learning achievement of class XI students of SMA Negeri 1 Pematangsiantar in the 2024/2025 Academic Year.The objectives of this study are: (1) To determine whether or not there is an influence of learning discipline and learning interest on the learning achievement of class XI students of SMA Negeri 1 Pematangsiantar in the 2024/2025 Academic Year.This type of research is a correlational study with the research population being 216 students of class XI of SMA Negeri 1 Pematangsiantar. Meanwhile, the sample in this study was 1 class, namely class XI-10, as many as 36 students. The instruments used in this study were the Learning Discipline and Learning Interest questionnaires and the PPKn Report Card scores of Class XI-10 of SMA Negeri 1 Pematangsiantar for the 2024/2025 Academic Year.All data from the two variables above were first tested whether they were normally distributed or not using a goodness-of-fit test or chi square and it turned out that both variables were normally distributed.The next step is to test the hypothesis by calculating the linear regression equation, namely Y over X1 is Ŷ = 78.048 + 0.65X1, meaning that between variable X1 is linear with Y and Y over X2 is Ŷ = 79.92 + 0.54X2, meaning that between variables X1 and X2 is linear with = 14.03 + 0.68X1 + 0.25X2.The coefficients of influence obtained are as follows:(1) The influence between X1 on Y is 0.82, (2) The influence between X2 on Y is 0.54, (3) The influence between X1 and X2 on Y is 0.69, (4) The Contribution Coefficient of Y on X1 is 67.24%, (5) The Contribution Coefficient of Y on X2 is 29.16%, (6) The Contribution Coefficient of X1 on X2 is 47.61%.Based on the hypothesis test, namely the significant influence test (t-test) by rejecting Ho and accepting H1, it is obtained: The influence of student learning discipline on student learning achievement in Civic Education subjects in class XI of SMA Negeri 1 Pematangsiantar in the 2024/2025 Academic Year. The influence of student learning interest on student learning achievement in Civic Education subjects in class XI of SMA Negeri 1 Pematangsiantar in the 2024/2025 Academic Year. The influence of learning discipline and learning interest together on student learning achievement in Civic Education subjects for class XI of SMA Negeri 1 Pematangsiantar in the 2024/2025 Academic Year.